2014
DOI: 10.29303/jbt.v14i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Kontroversi Produk Rekayasa Genetika Yang Dikonsumsi Masyarakat

Abstract: ABSTRAKRekayasa genetika adalah transplantasi satu gen ke gen lainnya baik antara gen danlintas gen untuk menghasilkan produk yang berguna bagi mahluk hidup hidup. Padaawalnya, rekayasa genetika hanya dilakukan pada tanaman untuk memecahkankekurangan pangan penduduk dunia, dan dalam pengembangannya rekayasa genetikatidak hanya berlaku untuk tanaman dan hewan yang serupa, tetapi telah berevolusi padamanusia dan lintas jenis. Prinsip dasar teknologi rekayasa genetika adalah memanipulasiperubahan komposisi asam n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
1
Order By: Relevance
“…Keunggulan bioteknologi modern di antaranya : perbaikan sifat genetik dilakukan secara terarah, dapat mengatasi kendala ketidaksesuaian genetik dan dapat meningkatkan kualitas produk. Perkembangan bioteknologi di Indonesia masih tergolong tertinggal jika dibandingkan dengan negara lain, hal ini disebabkan karena minimnya dana dan fasilitas penelitian, juga adanya kontroversi di bidang agama dan budaya (Mahrus, 2014).…”
Section: Pendahuluanunclassified
“…Keunggulan bioteknologi modern di antaranya : perbaikan sifat genetik dilakukan secara terarah, dapat mengatasi kendala ketidaksesuaian genetik dan dapat meningkatkan kualitas produk. Perkembangan bioteknologi di Indonesia masih tergolong tertinggal jika dibandingkan dengan negara lain, hal ini disebabkan karena minimnya dana dan fasilitas penelitian, juga adanya kontroversi di bidang agama dan budaya (Mahrus, 2014).…”
Section: Pendahuluanunclassified
“…20 GMO is basically a set of techniques that are used to manipulate genetic components which is Deoxyribonucleic acid (DNA) genome and genes 21 that can be performed in 1 (one) cell/organism or from one organism to another, even between different organisms. 22 Specifically, GMO's existence cannot be ignored in non-genetically engineered agricultural products. 23 Nevertheless, the main purpose of GMO development is to solve various food scarcity issues that are faced upon the world population, and it will remain unsolved conventionally due to the rapid population growth.…”
Section: Food Sovereignty and Genetically Modified Organismmentioning
confidence: 99%
“…Another problem is the possibility of killing other living things such as Lepidoptera larvae and microorganisms in the soil. This will impact the quantity and quality of crop production (Mahrus, 2014;Wasilah et al, 2019).…”
Section: Global Status and Transgenic Plants Controversymentioning
confidence: 99%
“…Agricultural cropping patterns in Indonesia are generally carried out in small areas surrounded by various weeds. With the crosspollination nature of GMO crops, there is a risk of new weeds being more resistant to herbicides (Mahrus, 2014). Losey et al (1999) reported higher mortality in monarch larvae when fed milkweed (their natural food supply) covered in pollen from transgenic corn than when fed milkweed from regular corn.…”
Section: Ethics In Transgenic Crop Engineeringmentioning
confidence: 99%